Protection-free one-pot synthesis of alcohol end-functionalized poly(3-hexylthiophene) - Choi, Hae Nam; Lee, In Hwan (Polymer Journal, 2021)
Alcohol end-functionalized poly(3-hexylthiophene) (P3HT-OH) is a high-value material used for the generation of conjugated P3HT-coil block copolymers via controlled polymerization methods. Previously, P3HT-OH was prepared by Kumada catalyst-transfer polycondensation, which required effort-intensive postpolymerization modifications and additional protecting group techniques. Herein, we report the direct one-pot synthesis of P3HT-OH by Suzuki-Miyaura catalyst-transfer polycondensation. Mild reaction conditions with good functional group tolerance allowed the preparation of well-defined P3HT-OH without protective groups or postmodification processes. Notably, the [Pd]/[alcohol initiator] ratio should be ≤1 to obtain well-defined P3HT-OH because at this ratio the oxidation of the alcohol group is suppressed, which reduces end-group fidelity. Moreover, the polymerization should be quenched before full conversion of the monomer to prevent disproportionation into P3HT dimers. The high end-group fidelity of P3HT-OH was confirmed by block copolymerization with polystyrene through atom-transfer radical polymerization. Our protocol provides facile access to P3HT-OH, which is useful for small-molecule functionalization and block copolymer synthesis.
Keywords: Block copolymer synthesis; Block copolymerization; Controlled polymerization; Kumada catalyst-transfer polycondensation; Mild reaction conditions; Poly (3-hexylthiophene); Postpolymerization modifications; Protecting group technique